Lost in optimisation of water distribution systems? A literature review of system operation. (July 2017) - Mala-Jetmarova, Helena; Sultanova, Nargiz; Savic, Dragan
Abstract: Optimisation of the operation of water distribution systems has been an active research field for almost half a century. It has focused mainly on optimal pump operation to minimise pumping costs and optimal water quality management to ensure that standards at customer nodes are met. This paper provides a systematic review by bringing together over two hundred publications from the past three decades, which are relevant to operational optimisation of water distribution systems, particularly optimal pump operation, valve control and system operation for water quality purposes of both urban drinking and regional multiquality water distribution systems. Uniquely, it also contains substantial and thorough information for over one hundred publications in a tabular form, which lists optimisation models inclusive of objectives, constraints, decision variables, solution methodologies used and other details. Research challenges in terms of simulation models, optimisation model formulation, selection of optimisation method and postprocessing needs have also been identified. Highlights: A review of operational optimisation of water distribution systems is provided. Future challenges were identified, despite the large body of existing literature. Universally agreed formulation of an operational optimisation problem is needed. Algorithm performance for a particular problem requires improved understanding. A method for selecting only one solution for a real system needs to be developed.